Cyber Extension: Penggunaan Media dan Kelancaran Pencarian Informasi di Kalangan Penyuluh Pertanian Kabupaten Bogor - Abung Supama Wijaya; Sarwititi Sarwoprasodjo; Diah Febrina (Institut Pertanian Bogor, 2019)
Current sustainable development of agriculture is one of which depends on the capacity of agricultural extension workers. The development of information technology contributes to the means for increasing this capacity. Cyber Extension, which is the embodiment of Law No. 16 of 2006 concerning agricultural extension systems, is expected to be fully utilized by extension agents throughout Indonesia. This is so that the instructors can provide information and develop innovations in agriculture. This study aims to explain the use of media and the stage of information seeking by instructors in Bogor district. The concept used in this research is Cyber Extension, media use and the smoothness of information retrieval. This study uses a quantitative descriptive approach with data collection techniques through surveys. A total of 61 agricultural instructors in Bogor Regency were interviewed through a closed questionnaire. In the media use variable, the results of the study show that the extension agent's ability to access is good while the availability of facilities and operational costs are still in the less category. When the smoothness of the information search process is in the smooth category.